Megaprepuce: presentation of a modified surgical technique with excellent cosmetic and functional results. Issue 4 (August 2019) - Hirsch, K.; Schwaiger, B.; Kraske, S.; Wullich, B.
Summary: Objective: Congenital megaprepuce is a malformation consisting of a great redundancy of the inner preputial skin over a penis with normal shaft and glans and is combined with a severe phimosis. Patients suffer from difficulties in voiding because the urine is trapped in the large dome-shaped megaprepuce. We describe a modification of the surgical technique of reconstructing a megaprepuce initially presented by Leao et al. Patients and methods: We retrospectively reviewed 7 patients aged 6–53 months (mean age 17 months, 6 were younger than 18 months) who underwent congenital megaprepuce repair between 02/2014 and 05/2018 in our institution. All these otherwise healthy children suffering from difficulties in voiding and reporting genital ballooning during micturition and urinary retention were referred to our hospital. In all cases, parents needed to express the trapped urine. Four of these patients additionally showed a glanular hypospadias, another one a distal penile hypospadias. In addition to the repair of the megaprepuce, six patients needed correction of a penile curvature, five of whom needed correction of the chordee and one a corporoplasty (Schröder-Essed). The patient showing the distal penile hypospadias additionally underwent hypospadias repair. During the follow-up, we evaluated the cosmetic result and complications such as secondary concealed penis, difficulties in voiding, urinary retention, and urinary infections. Results: Mean follow-up was 18 months. All patients following surgery showed normal voiding without urinary retention or urinary infections and good cosmetic results resembling a circumcised penis in appearance without reconcealment. No intraoperative complications occurred. One patient had a scrotal hematoma postoperatively. Mild transient edema of the penis was seen in all patients, which disappeared spontaneously within one week after surgery. Conclusion: Our surgical approach is a safe and relatively simple procedure with a low rate of complications, good cosmetic results, and functional outcome. Whether the hypospadias associated with ventral curvature was a coincidence or part of the disease pattern remains unclear but will probably be the object of further investigations. Image 1. Figure